Literacy Talent: Innovation in the Development of Busy Book Media to Improve Early Reading Ability in Kindergarten B Children 5-6 Years - Manola, Rezekita; ramadani, laili; dewi, ayu citra (Kiddie: Early Childhood Education and Care Journal, 2024)
Abstract: This research was motivated by problems found in the Islamic Kindergarten Grand Jihad Mosque in Padang Panjang, namely that children’s early reading development had monotonous activities and less interesting media so that children quickly felt bored when taking part in early reading lessons. This research aims to produce Busy Book learning media to stimulate the early reading abilities of children 5-6 years old which han been testd for suitability by Media Experts and Material Experts. This Research uses the Research & Development (R & D) method with the Thiagarajan 4D development model or Four-D model. The development procedure includes Define, Design, Develop and Disseminate. This research developed the Busy Book media with expert validation tests 2 validators and media trials on ten children aged 5-6 years in two meeting. The overall media validation results are in the “Very Feasible“category with a score percentage of 100%. The overall material validation results are in the “Very Feasible“category with a score percentage of 92.5 %. The results of field trials on 10 children obtained an increase of 45.83%, from 43.75% in the pre-test to 89.50% in the post-test with the “Very Feasible “category. Thus, the Busy Book learning process to stimulate the early reading abilities of children 5-6 years old. Keyywords: Busy Book, Media, Early Reading